Internship Report as Commercial, Project Operations and Strategy at Grab - Veronica, Cynthia; Ghazi, Muhammad; Detiana, Tita (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This internship report was aimed to explain Author’s activities during internship at Grab Indonesia through Magang Bersertifikat Kampus Merdeka Program held by the Ministry of Education. This program aims to provide opportunities for students to experience first-hand how to work and be involved professionally in a company. This report will explain about the Company, Author’s daily activities as part of Commercial, Project Operations and Strategy team and how the job are being divided. Beside daily activities about the job given, this report will explain other activities like internal training and engagement activities provided by People Organization team.